Trabalho e educação no Assentamento Guarani - Santos Neto, José Leite dos (Universidade Federal de São Carlos, 2014)
The agrarian reform settlements have been configured as a territory in costant dispute for capital, through agro-industrial partnerships, and are legalized by Ordinance state 77/2004, which allows the cultivation of the crops for agro-industrial ends at the state settlements of São Paulo, pointing them in a new direction. From this reality this essay has a goal to analyze the relation between Work and Education on these settlements, aiming to understand in which way the settled worker acquires the knowledge necessary for the production and how this agro-industrial knowledge interferes on the work developed. The field research was performed in the Guarani Settlement situated in the city of Pradópolis in the state of São Paulo, which has an agro-industrial partnership with a nearby plant, named Usina São Martinho. It was found that the work formation occurs mostly through experience and exchange of knowledge. This knowledge comes from previous generations, which were moved from the field and denied access to the land due to the technologic development which mechanized the field production. Few families have frequented schools. The search for knowledge about planting and crops also can be seen in the exchange of experiences with neighbors and even from practice itself. The technical advice from Institution ITESP and INCRA, due to the large number of families, has not been available for everyone. We concluded that the agro-industrial partnerships appear in the settlements after a process of exhausting the land of any other possibilities and are characterized as contradictory alternatives to the process of land struggle, although are accepted due to the precarious socioeconomic conditions of the people.
Keywords: Educação e trabalho; Parceria agro-industrial; Educação do campo; Assentamentos rurais; Work; Education; Field Education; Agro-Industrial partnerships; CIENCIAS HUMANAS::EDUCACAO